Longitudinal Assessment of Behaviour and Associated Bio-Markers Following Chronic Consumption of β-Sitosterol β-D-Glucoside in Rats: A Putative Model of Parkinson’s Disease - Bigelow, Logan J.; Perry, Melissa A.; Ogilvie, Sarah L.; Tasker, R. Andrew (Frontiers in Neuroscience, 2022)
The consumption of cycad (Cycas circinalis) seeds has been linked to the development of Amyotrophic Lateral Sclerosis-Parkinsonism Dementia Complex (ALS-PDC) in humans. ALS-PDC is a clinically variable disease presenting as a combination of symptoms typical of PD and/or ALS. Chronic consumption of β-sitosterol β-D-glucoside (BSSG), a component of the cycad seed, by rats (Rattus norvegicus) has been previously reported to initiate a progressive pathology that develops over several months and manifests as behavioural and histopathological changes that resemble characteristic features of Parkinson’s disease. As part of an independent multi-site validation study, we have tried to replicate and further characterize the BSSG model with a focus on motor function, and associated immunohistochemical markers. Beginning at 3 months of age, male CD® (Sprague Dawley) rats (N=80) were dosed orally with either a flour pellet or a flour pellet containing BSSG (3 mg) daily (5x/week) for 16 weeks consistent with previous reports of the model. Following BSSG intoxication, separate cohorts of animals (n=10/treatment) were exposed to a behavioural test battery at 16, 24, 32, or 40 weeks post initial BSSG feeding. The test battery consisted of the open field test, cylinder test, and ultrasonic vocalization (USV) assessment. No changes in behaviour were observed at any time point. Following behavioural testing, animals were processed for immunohistochemical markers of substantia nigra integrity. Immunohistochemistry of brain tissue revealed no differences in the microglial marker, Iba1, or the dopaminergic integrity marker, tyrosine hydroxylase (TH), in the substantia nigra at any assessment point. The absence of any group differences in behaviour and immunhistochemistry indicates an inability to replicate previous reports. Further investigation into the sources of variability in the model is necessary prior to further utilization of the BSSG model in preclinical studies.